The legitimacy of international organizations: The UNDP’s operations in Southern Africa - Pogoda, Magdalena (Zasadność tworzenia organizacji międzynarodowych na podstawie działania UNDP w regionie Afryki Południowej, 2021)
International organizations are specialized formal frameworks created to assist states in achieving national goals, stimulating economic growth, and ensuring the protection of their citizens, however their legitimacy has been questioned over the years. This paper aims to answer the question of the adequacy and effectiveness of one of such organizations, namely the United Nations Development Programme (UNDP) in the economic development of five countries in Southern Africa (Botswana, Eswatini, Lesotho, Namibia and South Africa). According to the analysis, the effects of the programme are satisfactory, although the intervention needs improvement. Southern African countries still lack stable and reliable statistical systems to monitor social and economic changes. In addition, these countries rely heavily on international organizations and do not take their own initiative, which makes all the endeavors less effective. Ultimately, these countries require both technical and expert support at all stages of the implemented projects to maximize the impact of the support and sustainability of the results. In line with these findings, the presence of the programme in the region seems to be justified, hence it actively contributes to its economic growth. Yet so far, no alternative ways of intervention have been found and the current framework, although imperfect, has not found a replacement.
Ekonomia XXI Wieku = Economics of the 21st Century, 2021, Nr 24, s. 56-88
Keywords: UNDP; UN; Southern Africa; economic development; ONZ; Afryka Południowa; rozwój gospodarczy